1998
DOI: 10.1002/masy.19981300129
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of polyorganosiloxanes

Abstract: Biodegradation of various polyorganosiloxanes (about 30 substances) under the influence of several biotype bacteria strain (16 types) were studied. A special procedure of biodegradation and analytical methods of evaluation the degree of degradation were applied. It was found that nearly all polysiloxanes tested are biodegradable but the degree of degradation depends on their composition and structure, as well as on the type of bacteria strain chosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…mirabilis is a Gram negative, facultative anaerobic bacterium. Along side, Pseudomonas aeruginosa, and Klebsiella pneumoniae, the organism has been reported to degrade organosilicone compounds [27]. While only few reports are available on the ability of the organism to decolorize azo dyes [28], no report exists to the best of our knowledge on its ability to mineralize such dyes.…”
Section: Resultsmentioning
confidence: 98%
“…mirabilis is a Gram negative, facultative anaerobic bacterium. Along side, Pseudomonas aeruginosa, and Klebsiella pneumoniae, the organism has been reported to degrade organosilicone compounds [27]. While only few reports are available on the ability of the organism to decolorize azo dyes [28], no report exists to the best of our knowledge on its ability to mineralize such dyes.…”
Section: Resultsmentioning
confidence: 98%
“…At the turn of 1970s, the possibility of their biodegradation has been proven. 48,49 Only few studies that focus on the biodegradation of various siloxanes have been reported. Nevertheless, the lack of studies did not affect the general assessment that polysiloxanes are a group of polymers that is difficult to biodegrade.…”
Section: Surface and Af Investigation Of The Nanocomposite Lmsmentioning
confidence: 99%
“…Nevertheless, the lack of studies did not affect the general assessment that polysiloxanes are a group of polymers that is difficult to biodegrade. 49 In this work, AF and biodegradation analysis was performed on the prepared PDMS/Cu 2 O nanocomposites as follows.…”
Section: Surface and Af Investigation Of The Nanocomposite Lmsmentioning
confidence: 99%
“…and Pseudomonas aeruginosa. Of them, P. aeruginosa is a facultative anaerobe that can proliferate with nitrate as a terminal electron acceptor and has been described as a siloxane-biodegrading species capable of producing biosurfactant molecules (Li et al, 2014;Rahman et al, 2002;Rościszewski et al, 1998).…”
Section: Lab-scale Btf Start Upmentioning
confidence: 99%